Does what happens abroad stay abroad? Displaced aggression and emotional regulation in expatriate psychological contracts. Issue 4 (1st October 2022) - Schuster, Tassilo; Bader, Anna Katharina; Bader, Benjamin; Rousseau, Denise M.
Abstract: The effects of psychological contract violation are the subject of considerable research. Yet, their effects in work arrangements with more than two parties are largely unknown. Multi‐party work arrangements differ from traditional ones because individuals may be vulnerable to psychological contract breach and violation by more than one party, potentially directing negative emotional responses not only towards the responsible party but also displacing it to the other (innocent) party. Primary data from a two‐wave survey of 221 current expatriates is used to test the effects of displaced aggression and emotion regulation in multi‐party psychological contracts. We find that the negative emotions (violation experiences) associated with breach predict reduced commitment both to the perpetrating organization and the innocent party. However, this spillover effect is asymmetric and follows displaced aggregation theory: Expatriates displace their aggressive behaviour on to the host when the home organization violated the psychological contract, not the reverse.